MELOXICAM SELF-NANOEMULSIFYING DRUG DELIVERY SYSTEM: FORMULATION AND RELEASE KINETICS ANALYSIS - AULIA, SALMA; WINARTI, LINA; WICAKSONO, YUDI (International Journal of Applied Pharmaceutics, 2021)
Objective: This study aimed to find the best SNEDDS meloxicam formula and analyze the release kinetics of meloxicam SNEDDS and non-SNEDDS using DDSolver. Methods: Meloxicam SNEDDS was prepared using sunflower seed oil, Cremophor RH 40 as a surfactant, and polyethylene glycol (PEG) 400 as a co-surfactant. Results: The best formula obtained subjected to the in vitro dissolution study was analyzed using DDSolver. The study shows one selected formula consists of 10% sunflower seed oil, 70% cremophor RH 40, and 20% PEG 400 with a 20.5 nm±12 nm droplet size. The dissolution study showed that SNEDDS could significantly increase the meloxicam release compared to the non-SNEDDS formulation. The kinetics of meloxicam release from SNEDDS formulations follow the Weibull release model (β = 1.00). Conclusion: This study concludes that SNEDDS best prepared in sunflower seeds oil: Chremophor RH 40: PEG 400 ratio of 1: 7: 2 and has the potency to increase the solubility and dissolution of meloxicam.